The Influence of Good Corporate Governance on the Financial Performance of Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2021-2023 - Fazila, Paula; Hijriah, Amanah; Rusliyawati (DINASTI RESEARCH, 2024)
This study aims to evaluate the impact of Good Corporate Governance (GCG) on the financial performance of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The research employs a quantitative method with an explanatory research type. Data were collected from annual reports and financial statements of companies using purposive sampling technique, resulting in a sample of 33 companies. Data analysis was conducted using SPSS software through several stages of testing. The findings indicate that institutional ownership has a significant positive impact on the financial performance of companies, as assessed through Return on Assets (ROA), while the independent board of commissioners has a significant negative impact and the audit committee shows no significant impact. Overall, GCG variables have a significant influence on the financial performance of companies, with institutional ownership playing a crucial role in enhancing management oversight.